The impact of COVID-19 on the orthopaedic patient in Slovenia: Hip and knee replacement surgery, 90-Day mortality, outpatient visits and waiting times - Levašič Vesna; Savarin Denia; Kovač Simon (Sciendo, 2022)
The purpose of the study was to analyse the impact of the COVID-19 pandemic on the healthcare of the orthopaedic patient, i.e. numbers of hip and knee replacement surgeries, 90-day mortality, waiting times and outpatient clinic visits.